Analogical model tests on repeated surficial failure of dry granular slopes confined by retaining walls - Yang, Hufeng; Xing, Bencong; Jiang, Hu; Cheng, Qiangong (Frontiers in Earth Science, 2022)
In alpine and gorge regions, surficial failure of granular slopes has seriously affected infrastructure construction and the safe operation of transportation networks. This research focuses on dry granular slopes confined by retaining walls. Repeated surficial failure of granular slopes has been explored through indoor physical model tests. The results show that surficial failure presents low frequency and large scale for granular slopes dominated by coarse particles. The mass of debris that crosses retaining walls indicates activity level of granular slopes. When this mass for each surficial failure gradually decreases, it is highly likely that large-scale surficial failure will occur. As the amount of debris deposited on the slope increases, it is probable that the debris mass falling during a massive sliding event will be many times that of the previous sliding event. In engineering practice, it is necessary during road cleaning processes to record the volume of debris accumulated on the road. A continuous increase in the slope angle indicates a high probability of large-scale surficial failure. For each granular slope with a unique particle composition, there is a critical change rate for early warning of surficial failure, which can be determined by long-term monitoring.